IPTEKS PROSES PENGELOLAAN LAPORAN KEUANGAN PADA BADAN PERENCANAAN PEMBANGUNAN PENELITIAN DAN PENGEMBANGAN DAERAH (BAPELITBANGDA) KOTA MANADO - Rondonuwu, Clarissa B.; Kindangen, Wulan D. (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
The Manado City Planning, Development, Research and Development Agency (BAPELITBANGDA) is an agency or institution that assists the Mayor in supporting everything related to Planning, Development, Research, Development, and under the leadership of the head of the agency. The purpose of this study is that we can find out the process of managing financial statements from the Planning, Development, Research and Development Agency of the City of Manado. Because in each activity or program implemented requires funds to support the smooth running of the planned activities. Therefore, financial statements are very necessary for an institution because it is very useful in assessing a financial condition in all activities carried out. Thus, the applicable accounting principles are needed, so that the financial report management process can run well and efficiently.Keywords: financial report management process, BAPELITBANGDA Manado City